Climate change alters the haemolymph microbiome of oysters. (March 2021) - Scanes, Elliot; Parker, Laura M.; Seymour, Justin R.; Siboni, Nachshon; King, William L.; Danckert, Nathan P.; Wegner, K. Mathias; Dove, Michael C.; O'Connor, Wayne A.; Ross, Pauline M.
Abstract: The wellbeing of marine organisms is connected to their microbiome . Oysters are a vital food source and provide ecological services, yet little is known about how climate change such as ocean acidification and warming will affect their microbiome. We exposed the Sydney rock oyster, Saccostrea glomerata, to orthogonal combinations of temperature (24, 28 °C) and p CO2 (400 and 1000 μatm) for eight weeks and used amplicon sequencing of the 16S rRNA (V3-V4) gene to characterise the bacterial community in haemolymph. Overall, elevated p CO2 and temperature interacted to alter the microbiome of oysters, with a clear partitioning of treatments in CAP ordinations. Elevated p CO2 was the strongest driver of species diversity and richness and elevated temperature also increased species richness. Climate change, both ocean acidification and warming, will alter the microbiome of S . glomerata which may increase the susceptibility of oysters to disease. Highlights: Elevated p CO2 and temperature caused shifts in the oyster haemolymph microbiome. Elevated p CO2 was the strongest driver of species diversity and richness. Elevated p CO2 and temperature caused a loss of "core" bacteria. There was no evidence for a shift in the microbiome from a mutualistic to pathogenic state.